2020
DOI: 10.1140/epjd/e2020-10081-0
|View full text |Cite
|
Sign up to set email alerts
|

Dependence upon charge of the vibrational spectra of small Polycyclic Aromatic Hydrocarbon clusters: the example of pyrene

Abstract: Infrared spectra are computed for neutral and cationic clusters of Polycyclic Aromatic Hydrocarbon clusters, namely (C16H10) (0/+) n=1,4 , using the Density Functional based Tight Binding scheme combined with a Configuration Interaction scheme (DFTB-CI) in the double harmonic approximation. Cross-comparison is carried out with DFT and simple DFTB. Similarly to the monomer cation, the IR spectra of cluster cations are characterized by a depletion of the intensity of the CH stretch modes around 3000 cm −1 , with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 90 publications
(129 reference statements)
1
14
0
Order By: Relevance
“…We have shown that this simple scheme provides similar results to those obtained with the Charge Model approach to model clusters of PAHs [31] and water [32].…”
Section: Dftbsupporting
confidence: 58%
“…We have shown that this simple scheme provides similar results to those obtained with the Charge Model approach to model clusters of PAHs [31] and water [32].…”
Section: Dftbsupporting
confidence: 58%
“…Moreover, it is noteworthy in Figure 4a that the decay of (C16H10)2 + ions of internal energy above 1.45 eV have negligible contributions to the total neutral yield at the time of 1.0 ms at which the laser pulses were fired to perform the photodissociation spectrum. Using the harmonic vibrational modes calculated by Dontot et al (43) and the Beyer-Swinehart algorithm for harmonic oscillators (44), we can derive from this energy a maximum microcanonical temperature of ~480 K. We do not expect a thermal equilibrium of the ions produced within the plasma source. Therefore, it is difficult to derive a corresponding canonical temperature for the population of ions.…”
Section: Resultsmentioning
confidence: 90%
“…These timescales can be compared with those of the pyrene dimer vibrational modes as an efficient energy transfer would be favored by similar orders of magnitudes. The intermolecular dimer modes possibly mixed with very soft folding modes are lying within the 70-120 cm −1 spectral range [61] with corresponding half-periods of 130-240 fs. These timescales are of the same order of magnitude as the time for the Argon to travel across the largest pyrene axis for collision energies below 10 eV.…”
Section: Kinetic Energy Proportion (%)mentioning
confidence: 96%
“…Most of the theoretical studies involve neutral clusters, mostly due to the fact that treating charge resonance process in ions is a challenging task for DFT based methods [58]. One should however mention recent studies computing ionisation potentials [20] as well as structural [59] and spectral (electronic [60] and vibrational [61]) properties of cations, performed with an original model combining density functional based tight binding (DFTB) [62][63][64][65] with a configuration interaction scheme [66].…”
Section: Introductionmentioning
confidence: 99%